A look at the regulatory complex and the role of primary care in the care process (Research, Society and Development, 2022)
The National Regulatory Policy is a management strategy aimed at organizing the Brazilian health system, improving available resources, qualifying the population's attention and access to health actions and services. This study aims to discuss the health regulation process and the role of primary care health professionals in the system's solvability. This is a literature review research. For collection, the following criteria were used: Situational diagnosis of primary care, Criteria for access to the regulation system and Research that supports the relationship between primary care, professionals and the process of regulation of specialized procedures. The material was acquired by the Electronic Library Scientific Electronic Library Online (SciELO), Ordinances of the Ministry of Health (MS) regarding the Primary Care Policy and National Health Regulation Policy and municipal bylaws. As a result, it can be seen that health professionals in the scope of primary care are considered the articulators of the care network and considers the System of Regulation of Procedures a fundamental management strategy to guarantee the rights of users in accordance with the principles of the SUS. Therefore, it is necessary to present a relationship between the information available in information systems and the primary care service, a process achieved with the permanent education strategy, since health professionals who are able to effectively articulate the demand process existing in the primary system for the specialized service allows to minimize the drowning of the entire health system.